A lightning bolt. The activity of Bruno Zevi in post-war Italy - Ghia, Maria Clara (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2018)
This essay focuses on Bruno Zevi’s working period immediately after Second World War, coming back to Italy after his stay in London and in the USA. He starts right away his impressive attempt of popularizing contemporary architecture through “Metron”, the first magazine to be printed in Italy after the war, from 1945 to 1954. In this crucial phase he founded the APAO (Association for Organic Architecture), he contributed to the editing of the Manuale dell'Architetto (an handbook with all the new construction and ready-assembly techniques), he published Verso un'architettura organica (1945), Saper vedere l'architettura (1948) and Storia dell'architettura moderna (1950), he curated the first Frank Lloyd Wright exhibit in Italy and he greatly contributed to the spreading of modern architecture and urbanism all around the country. Zevi also paying special attention to social issues, raised the question of inner spaces where man lives and where the collective theme is expressed, and stressed the need of shaping the building in the name of human use and enjoyment.
Keywords: Space; history of architecture; organic architecture; Reconstruction; Frank Lloyd Wright